Proceedings of the 1999 ACM SIGMETRICS International Conference on Measurement and Modeling of Computer Systems 1999
DOI: 10.1145/301453.301482
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimizing I/O throughput of multiple disks on a bus

Abstract: In modern I/O architectures, multiple disk drives are attach e d t o e a c h I/O controller. A study of the performance of such a r c hitectures under I/O-intensive w orkloads has revealed a performance impairment that results from a p r eviously unknown form of convoy behavior in disk I/O. In this paper, we describe measurements of the read performance of multiple disks that share a SCSI bus under a heavy workload, and develop and validate formulas that accurately characterize the observed performance (to wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
(6 reference statements)
0
12
0
Order By: Relevance
“…3, which is the main contribution of our work, do not depend on a particular structure of the function T (s i ). Nevertheless, we describe here a specific form based on past research on HDD I/O throughput [3] [4], and based on our performance study of disk access time observed in caching servers. We will refer to this specific form later to clarify some properties of the optimal policy.…”
Section: Hard Disk Service Timementioning
confidence: 99%
See 1 more Smart Citation
“…3, which is the main contribution of our work, do not depend on a particular structure of the function T (s i ). Nevertheless, we describe here a specific form based on past research on HDD I/O throughput [3] [4], and based on our performance study of disk access time observed in caching servers. We will refer to this specific form later to clarify some properties of the optimal policy.…”
Section: Hard Disk Service Timementioning
confidence: 99%
“…A consequence of such decoupling is that, at any time, the RAM stores a subset (M R ) of the contents stored in the HDD (M H ). 3 In our work we consider the same decoupling principle. As a consequence, our policy is agnostic to the replacement policy implemented at the HDD (LRU, FIFO, Random, .…”
Section: Problem Formulationmentioning
confidence: 99%
“…The seek minimization properties of physical mirroring with 2 disks with respect to the nearest server algorithm have been studied extensively in [12] and [21]. As we noted there are many other papers which deal with this and related subjects which contain a basic error [5], [6], [7], [9], [10], [26], [25], [28], [29]. Among those whose results remain qualitatively correct despite the error one should note [25] which considers synchronous writes as well as reads and [26] which provides a comparison of online and offline algorithms all assuming physical mirroring.…”
Section: Related Workmentioning
confidence: 99%
“…Algorithmic performance with data stored on disk has been studied extensively in external memory models (c.f. [26,23,3]). These models usually consider block-oriented devices with varying degrees of precision (e.g., including modeling parallelism, drive geometry, memory hierarchies, caching, locality of blocks, etc.).…”
Section: Introductionmentioning
confidence: 99%